The Pareto-Frontier in a Simple Mirrleesian Model of Income Taxation - Felix Bierbrauer; Pierre C. Boyer (Center for Economic Studies and ifo Institute (CESifo), 2013)
We characterize the Pareto-frontier in a simple Mirrleesian model of income taxation. We show how the second-best frontier which incorporates incentive constraints due to private information on productive abilities relates to the first-best frontier which takes only resource constraints into account. In particular, we argue that the second-best frontier can be interpreted as a Laffer-curve. We also use this second-best frontier for a comparative statics analysis of how optimal income tax rates vary with the degree of inequity aversion, and for a characterization of optimal public-good provision. We show that a more inequity averse policy maker chooses tax schedules that are more redistributive and involve higher marginal tax rates, while simultaneously providing less public good.
Keywords: H21; H41; D82; 330; optimal income taxation; Laffer-curve; public-good provision